Impact of IL-17A Inhibitors on Serum Uric Acid Levels in Psoriatic Patients with Hyperuricemia: A Prospective Observational Study - Wu C; He C; Wang H; Wang W; Jin H (Psoriasis: Targets and Therapy)
Chao Wu,* Chunxia He,* Haimeng Wang, Wenming Wang, Hongzhong Jin Department of Dermatology, State Key Laboratory of Complex Severe and Rare Diseases, Peking Union Medical College Hospital, Chinese Academy of Medical Sciences and Peking Union Medical College, National Clinical Research Center for Dermatologic and Immunologic Diseases, Beijing, People’s Republic of China*These authors contributed equally to this workCorrespondence: Hongzhong Jin, Department of Dermatology, Peking Union Medical College Hospital, Chinese Academy Medical Science and Peking Union Medical College, No. 1 Shuai Fu Yuan Street, Beijing, 100730, People’s Republic of China, Fax +86-10-6915-1502, Email jinhongzhong@263.netPurpose: This prospective observational study investigated whether interleukin (IL)-17A inhibitors could reduce serum uric acid (SUA) levels in psoriatic patients with hyperuricemia. It also explored the risk factors for hyperuricemia in psoriatic patients and the effectiveness of IL-17A inhibitors for the skin lesions of psoriatic patients with hyperuricemia.Methods: Patients aged ≥ 18 years with moderate to severe plaque psoriasis along with concomitant hyperuricemia (defined as an SUA level > 416 μmol/L in men and > 357 μmol/L in women) at baseline were treated with either secukinumab or ixekizumab. SUA levels were longitudinally assessed over 1 year. We evaluated the changes in SUA level and factors associated with SUA changes. Binary logistic regression was conducted to identify risk factors for hyperuricemia in psoriatic patients. Additionally, we examined effectiveness of IL-17A inhibitors for patients with psoriasis and hyperuricemia including Psoriasis Area Severity Index (PASI) 75, 90, and 100 response rates at 1 year.Results: Our study included 196 individuals diagnosed with psoriasis and hyperuricemia. The mean SUA levels were 481± 68 μmol/L at baseline and 442± 78 μmol/L after 1 year of treatment with IL-17A inhibitors (p< 0.001). Subgroup analysis revealed a consistent and significant decrease in SUA levels across different genders, age groups (30– 39, 40– 49, ≥ 50 years), BMI categories, baseline PASI scores, PASI improvement rates, and among patients treated with different IL-17A inhibitors. Patients aged ≥ 50 years and with a BMI < 24 exhibited a higher SUA reduction rate. Male gender, age under 40 years, obesity, hypertension, hypertriglyceridemia, and a PASI score of ≥ 20 were independent risk factors for hyperuricemia in patients with psoriasis. The PASI 75, 90, and 100 response rates in psoriatic patients with hyperuricemia were 88.3%, 60.2%, and 28.6%, respectively, after 1 year of treatment with IL-17A inhibitors.Conclusion: Our findings suggest that SUA levels decrease significantly under IL-17A inhibitors treatment in psoriatic patients with hyperuricemia. Patients aged ≥ 50 years and with a BMI < 24 had greater benefits. This study provides a theoretical basis for the selection of biologics to treat psoriatic patients with hyperuricemia.Keywords: psoriasis, uric acid, hyperuricemia, IL-17A inhibitor